Altered intestinal microbiota enhances adenoid hypertrophy by disrupting the immune balance - Liu, Wenxin; Jiang, Huier; Liu, Xiling; Zheng, Yue; Liu, Yanan; Pan, Fen; Yu, Fangyuan; Li, Zhi; Gu, Meizhen; Du, Qingqing; Li, Xiaoyan; Zhang, Hong; et al. (Frontiers in Immunology, 2023)
This is a provisional file, not the final typeset articleIn AH individuals, only a slight decrease of diversity in bacterial community was found, while significant changes of microbial composition were observed between these two groups. Compared with HCs, decreased abundances of Akkermansia, Oscillospiraceae and Eubacterium coprostanoligenes genera and increased abundances of Bacteroides, Faecalibacterium, Ruminococcus gnavus genera were revealed in AH patients. The abundance of Bacteroides remained stable with age in AH children. Notably, a microbial marker panel of 8 OTUs were identified, which discriminated AH from HC individuals with an area under the curve (AUC) of 0.9851 in the discovery set, and verified in the geographically different validation set, achieving an AUC of 0.9782. Furthermore, transfer of mice with fecal microbiota from AH patients dramatically reduced the proportion of Treg subsets within peripheral blood and nasal-associated lymphoid tissue (NALT) and promoted the expansion of Th2 cells in NALT.These findings highlight the effect of the altered gut microbiota in the AH pathogenesis.